Step 1:
Start by putting
![\frac{d}{dx}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bd%7D%7Bdx%7D%20)
in front of each term
![\frac{d}{dx}[y cos x]= \frac{d}{dx}[5x^2]+ \frac{d}{dx}[ 3y^2]](https://tex.z-dn.net/?f=%20%5Cfrac%7Bd%7D%7Bdx%7D%5By%20cos%20x%5D%3D%20%5Cfrac%7Bd%7D%7Bdx%7D%5B5x%5E2%5D%2B%20%5Cfrac%7Bd%7D%7Bdx%7D%5B%203y%5E2%5D)
-----------------------------------------------------------------------------------------------------------------
Step 2:
Deal with the terms in 'x' and the constant terms
![\frac{d}{dx}[ycosx]= 10x+ \frac{d}{dx} [3y^2]](https://tex.z-dn.net/?f=%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bycosx%5D%3D%2010x%2B%20%5Cfrac%7Bd%7D%7Bdx%7D%20%5B3y%5E2%5D%20%20)
----------------------------------------------------------------------------------------------------------------
Step 3:
Use the chain rule for the terms in 'y'
![\frac{d}{dx}[ycosx]=10x+6y \frac{dy}{dx}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bycosx%5D%3D10x%2B6y%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%20)
--------------------------------------------------------------------------------------------------------------
Step 4:
Use the product rule on the term in 'x' and 'y'
![(y) \frac{d}{dx} cos x+(cos x) \frac{d}{dx}y =10x+6y \frac{dy}{dx} ](https://tex.z-dn.net/?f=%28y%29%20%5Cfrac%7Bd%7D%7Bdx%7D%20cos%20x%2B%28cos%20x%29%20%5Cfrac%7Bd%7D%7Bdx%7Dy%20%3D10x%2B6y%20%5Cfrac%7Bdy%7D%7Bdx%7D%0A)
![y(-siny)+(cosx) \frac{dy}{dx} =10x+6y \frac{dy}{dx}](https://tex.z-dn.net/?f=y%28-siny%29%2B%28cosx%29%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D10x%2B6y%20%5Cfrac%7Bdy%7D%7Bdx%7D%20)
--------------------------------------------------------------------------------------------------------------
Step 5:
Rearrange to make
![\frac{dy}{dx}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bdy%7D%7Bdx%7D%20)
the subject
![-y sin(y)+cos(x) \frac{dy}{dx} =10x+6y \frac{dy}{dx}](https://tex.z-dn.net/?f=-y%20sin%28y%29%2Bcos%28x%29%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D10x%2B6y%20%5Cfrac%7Bdy%7D%7Bdx%7D%20)
![cos(x) \frac{dy}{dx}-6y \frac{dy}{dx}=10x+y sin(y)](https://tex.z-dn.net/?f=cos%28x%29%20%20%5Cfrac%7Bdy%7D%7Bdx%7D-6y%20%5Cfrac%7Bdy%7D%7Bdx%7D%3D10x%2By%20sin%28y%29%20%20)
![[cos(x) - 6y] \frac{dy}{dx}=10x + y sin(y)](https://tex.z-dn.net/?f=%5Bcos%28x%29%20-%206y%5D%20%20%5Cfrac%7Bdy%7D%7Bdx%7D%3D10x%20%2B%20y%20sin%28y%29%20)
![\frac{dy}{dx}= \frac{10x+ysin(y)}{cos(x)-6y}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bdy%7D%7Bdx%7D%3D%20%5Cfrac%7B10x%2Bysin%28y%29%7D%7Bcos%28x%29-6y%7D%20%20)
⇒ Final Answer
Step-by-step explanation:
5. answer ➡D
6 . answer ➡A
8 . answer ➡C
Answer:
x<-1
Step-by-step explanation:
-4x+8>12
-4x>12-8
-4x>4
x>4/-4
x>-1
x<-1
Answer:
The last one
Step-by-step explanation:
measure angle 2 and 6 to see if congruent
Answer:
613.8 meters cubed
Step-by-step explanation:
6.2x11x9=exactly 613.8 meters cubed